2020
DOI: 10.1002/asia.202000547
|View full text |Cite
|
Sign up to set email alerts
|

Functional Zwitterionic Polymers on Surface: Structures and Applications

Abstract: Zwitterionic polymers are important in a wide range of industrial, biological and medical fields. Their chemical structures include an equal amount of anion and cation groups, and such structures give rise to many unique functionalities, such as temperature response, anti-polyelectrolyte effect, and strong hydration properties. In this review, we focus on the structures and applications of functional zwitterionic polymers on surfaces. We review three areas of applications according to the architecture of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 113 publications
1
46
0
Order By: Relevance
“…Known as the antipolyelectrolyte effect, salt ions can shield charges in zwitterionic polymers. This leads to an increase in solubility and thus a sharp drop in UCST until the thermoresponsive behavior eventually disappears completely even at relatively low ionic strength [ 50 , 281 , 322 ]. This phenomenon still hinders the wide use of zwitterionic polymers in physiological media for biomedical applications, although they have long been known for their sharp and reversible UCST-type behavior in water.…”
Section: Reviewmentioning
confidence: 99%
“…Known as the antipolyelectrolyte effect, salt ions can shield charges in zwitterionic polymers. This leads to an increase in solubility and thus a sharp drop in UCST until the thermoresponsive behavior eventually disappears completely even at relatively low ionic strength [ 50 , 281 , 322 ]. This phenomenon still hinders the wide use of zwitterionic polymers in physiological media for biomedical applications, although they have long been known for their sharp and reversible UCST-type behavior in water.…”
Section: Reviewmentioning
confidence: 99%
“…Since many researchers have reported that zwitterionic polymers show antifouling effects, they have been used for coating surfaces of medical devices and drug delivery systems. [ 1–4 ] Moreover, some zwitterionic polymers afford upper critical solution temperature (UCST)‐type temperature‐sensitive properties; hence, they are applicable as smart materials. [ 3,4 ] Hydrogels fabricated from zwitterionic polymers also show antifouling and thermosensitive properties; hence, they have been used as implant materials, temperature‐responsive drug containers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3,4 ] Hydrogels fabricated from zwitterionic polymers also show antifouling and thermosensitive properties; hence, they have been used as implant materials, temperature‐responsive drug containers, etc. [ 1–3 ] Since zwitterionic polymers interact with each other due to the electrostatic interactions, zwitterionic polymer hydrogels exhibit self‐healing properties. [ 1–3 ] Thus, they have great potential for various kinds of applications, especially in biomedical fields.…”
Section: Introductionmentioning
confidence: 99%
“…The commercial interest for these polymers is determined by their possibility to be used as polymeric sorbents, oil recovery agents, fungicides, flame retardant polymers, emulsifying agents, wetting agents, cleaning agents and cryoprotectants [23][24][25]. Polymers having various betaine structure were synthesized in order to obtain materials sensitive to different stimuli (pH, temperature, etc.)…”
Section: Introductionmentioning
confidence: 99%